Acute menopausal symptoms in young cancer survivors immediately following chemotherapy - Cameron, Katherine E. (Oncology, 2018)
PURPOSE: To evaluate the prevalence of menopausal symptoms in young cancer survivors immediately following the completion of chemotherapy METHODS: This prospective cohort study followed 124 young females with a new diagnosis of cancer requiring chemotherapy to assess symptoms of menopause pre-treatment and immediately following chemotherapy. Symptoms were compared pre versus post treatment using McNemar’s test and between cancer patients and 133 similar-aged healthy controls using Pearson Chi-squared and exact tests. RESULTS: Participants undergoing cancer therapy reported more menopausal symptoms compared to controls prior to the initiation of any treatment (hot flashes or night sweats 33 vs 7% p<0.01, trouble sleeping 57 vs 31% p<0.01, headaches 50 vs 35% p=0.02, and decreased libido 36 vs 16% p<0.01) and also reported greater prevalence of symptoms immediately after cancer therapy compared to pre-treatment prevalence (vasomotor symptoms p<0.01, vaginal dryness p<0.01, decreased concentration p<0.01, and body aches p=0.01). Cancer patients with lower AMH levels after treatment (<0.10ng/mL) had an increased risk of vasomotor symptoms (OR=2.2, p=0.04), mood swings (OR 2.4, p=0.03), feeling sad (OR 2.2, p=0.04), trouble sleeping (OR 2.7, p=0.02) and decreased libido (OR 3.0, p=0.03) when controlled for age and cancer type, and the incidence of these symptoms was not affected by the use of systemic hormones or psychiatric medications. Treatment length, use of alkylating agents, pelvic radiation, and marital status were also not associated with the prevalence of menopausal symptoms. CONCLUSIONS: Pre-menopausal women with a new cancer diagnosis have more menopausal symptoms than females of similar age before and after cancer treatment, the effects of which are not mitigated by systemic hormone use. Decreased AMH levels were associated with an increased likelihood of reporting physiologic symptoms after therapy. IMPLICATIONS FOR CANCER SURVIVORS: This information is imperative for counseling, and ultimately, improved symptom management during and after cancer therapies will improve quality of life in young cancer survivors.